Introduction and Use of Aloe Vera-Based Edible Coating to Improve the Quality of Cucumber Fruit in the Oemanas Farmer Group Nian Village: Pengenalan dan Penggunaan Edible Coating Berbasis Aloe Vera untuk Peningkatan Mutu Buah Timun di Kelompok Tani Oemanas Desa Nian - Risna Erni Yati Adu; Marselina Theresia Djue Tea; Gebhardus Djugian Gelyaman (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Cucumber is one of the main commodities produced by the Oemanas Farmers Group in Nian Village. So far, the number of cucumbers produced is quite high during harvest time, but often experiences physical damage during transportation and marketing. Due to the limited knowledge and skills of the farmer group members, so far there has been no post-harvest processing and preservation technique. As an effort to reduce this problem, it is necessary to carry out activities to introduce and apply edible coating based on easily accessible materials. Edible coating can control post-harvest damage to cucumbers. This community service activity aims to control damage to cucumbers in partner groups through preliminary survey activities to obtain information related to partner conditions, socialization in the form of lectures followed by interactive discussions between participants and implementers, training in preparation and application of coating suspensions carried out through demonstration activities then continued with independent practice activities by each member of the farmer group. The final activity is an evaluation to measure the achievement of the goals and targets of the activity. The evaluation results showed an increase in partner knowledge about edible coating by 65% ​​of the total participants. In addition, more than 70% of partner members have the skills to carry out the preparation of edible coating suspensions and apply them to the surface of cucumbers through dipping techniques.